(untitled) (Bangladesh Agronomy Journal, 2023)
Proline (Pro) and glycine betaine (GB) act as significant osmoprotectants, potentially mitigating the detrimental effects of various abiotic stresses in plants. Given the growth-enhancing capabilities and other regulatory roles of Pro and GB, the current study was conducted to assess their function in imparting salt stress resilience in proso millet (Panicum miliaceum L). Proso millet plants were subjected to two levels of salt stress (S1 = 150 mM; S2 = 300 mM). Foliar applications of Pro (0.5 mM) and GB (0.5 mM) were provided under control and salt-stressed conditions at 10-day intervals twice. Compared to control conditions, plant growth, fresh and dry weight, leaf relative water content (RWC), SPAD value, and yield-contributing attributes noticeably decreased under salt stress. In contrast, plants supplemented with Pro and GB exhibited enhanced characteristics. Moreover, growth and yield parameters improved in salt-treated proso millet plants when supplemented with Pro and GB. These results suggest that the foliar application of Pro and GB can alleviate salt-induced oxidative stress in proso millet plants by modulating the antioxidative defense. Bangladesh Agron. J. 2023, 26(1): 75-83